Location of a single beta-tubulin gene product in both cytoskeletal and mitotic-spindle microtubules in Physarum polycephalum. - Paul, E; Burland, T; Gull, K (1989)
In the mutant BEN210 of Physarum polycephalum several beta-tubulins are detectable. beta 1-tubulin is unique to the myxamoeba, beta 2-tubulin is unique to the plasmodium, and the mutant beta 1-210 tubulin encoded by the benD210 allele is present in both cell types. In order to analyse the subcellular distribution of the beta 1-210 polypeptide, we prepared cytoskeletons from myxamoebae and mitotic spindles from plasmodia, and examined the tubulin polypeptide composition of these microtubular organelles by two-dimensional gel electrophoresis and immunoblotting. The results show that the beta 1-210 tubulin is present in microtubules of both the cytoskeleton and the intranuclear mitotic spindle. Thus a single beta-tubulin gene product can participate in multiple microtubular organelles in distinct cellular compartments.